2015
DOI: 10.1088/0953-4075/48/8/082001
|View full text |Cite
|
Sign up to set email alerts
|

Interatomic and intermolecular Coulombic decay: the coming of age story

Abstract: In pioneering work by Cederbaum et al an excitation mechanism was proposed that occurs only in loosely bound matter (Cederbaum et al 1997 Phys. Rev. Lett. 79 4778): it turned out, that (in particular) in cases where a local Auger decay is energetically forbidden, an excited atom or molecule is able to decay in a scheme which was termed 'interatomic Coulombic decay' (or 'intermolecular Coulombic decay') (ICD). As ICD occurs, the excitation energy is released by transferring it to an atomic or molecular neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
158
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(159 citation statements)
references
References 148 publications
0
158
1
Order By: Relevance
“…Nowadays the interatomic Coulombic decay is recognized as a highlyefficient elementary process in numerous physical and chemical systems [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays the interatomic Coulombic decay is recognized as a highlyefficient elementary process in numerous physical and chemical systems [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…[1] -this slogan summarizes the nearly twenty years of success history of the ultrafast interatomic (intermolecular) Coulombic decay (ICD) process from its first theoretical prediction by Cederbaum, Zobeley, and Tarantelli [2] to its widespread theoretical and experimental observation [3,4] in various atomic and molecular systems including clusters of noble gas atoms [5,6,7,8], endohedral fullerenes [9,10,11], aqueous solutions [12,13,14,15,16,17], biological systems [18,19,20,21,22,23], and nanomaterials [24,25,26] just to name a few.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of time-resolved electron dynamics in various atomic, molecular, and condensed-matter reactions have increased over the past two decades [1][2][3][4][5][6][7] owing to experimental progress in generating ultrashort and/or intense pulses of extreme ultraviolet light [8,9], x rays [10,11], and electrons [12,13]. These advances open the possibility of obtaining a deeper understanding of physical and chemical reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Followup studies during the recent years showed that ICD is not an exotic process, but rather a very common decay route in the nature as it occurs after excitation by photons [2][3][4], electrons [5], and ions [6] and in differently bound systems from van der Waals clusters such as the extreme case of He 2 [7] to systems consisting of hydrogen bonds such as water [8,9]. An experimentalist point of view review of the "early years of ICD" can be found in [10] and of more recent studies in [11]. Two comprehensive theoretical review papers by Santra et al [12] and Averbukh et al [13] are available, as well.…”
Section: Introductionmentioning
confidence: 99%